We rewrite the expression differently making sin^2(x) appears

sin^5(x)*cos^2(x)=sin(x)*sin^2(x)*sin^2(x)*cos^2(x)

We remplace sin^2(x) by 1 - cos^2(x) as it's equal

so sin^5(x)*cos^2(x)=sin(x)*(1-cos^2(x))*((1-cos^2(x))*cos^2(x)

=sin(x)*(1-cos^2(x))(cos^2(x)-cos^4(x))=sin(x)(cos^2(x)-cos^4(x)-cos^4(x)+cos^6(x))

=sin(x)(cos^2(x)-2cos^4(x)+cos^6(x))

That's it.

Thanks man

You are welcome

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up